CULTURAL COMMUNICATION-ENCOUNTER OF THE ST. THOMAS CHRISTIANS WITH THE HINDUS IN KERALA - Mundadan, A Mathias (Journal of Dharma, 1999)
The ancient Christians of Kerala very early in their existence developed a lifestyle. This life style, in Church matters reflected to some extent the pattern of the Persian Christians. In the socio-cultural realm it was not different from that of their Hindu neighbours. In the social set-up of Kerala they emerged as the peers of the higher classes, especially the Nayars. The long experience they had acquired of the Hindu way of life and the good neighbourly relations they maintained with the Hindu brethren enabled them to build up a more positive approach towards Hinduism and Hindu practices. Their integration to the socio-cultural milieu of Kerala was most satisfying. How far this integration reflected in their spiritual life, worship, Christian thinking, Church structure, etc, is problematic. The Yogam or Church Assembly at the local as well as at the general level and the position of the Archdeacon, who appears always to have been the national leader of the community, was a unique characteristic of the Kerala society.